Renal dysfunction due to surgical stress and its effects on survival in patients aged 90 and over: Risk of renal dysfunction in patients aged 90 years and older - Kutlusoy, Sevgi; Koca, Erdinç; Aydın, Ahmet (Journal of Surgery and Medicine, 2023)
Background/Aim: Published studies of surgical outcomes in patients aged 90 years and older have mostly focused on specific surgeries such as hip fractures. Unlike previous reports, our study includes all surgical procedures in patient groups aged 90 and over for eight years in our hospital. We aim to be able to predict the responses of an older adult’s kidney due to surgical stress by using the values of plasma urea and creatine, which are preoperative and postoperative routine laboratory parameters, and to predict its effect on mortality. Methods: Our study was conducted as a retrospective cohort study with 284 patients whose ages ranged from 90 to 119 and who had undergone a surgical operation. The patients were divided into four groups according to preoperative and postoperative creatinine values: preoperative and postoperative creatinine <1.25 mmol/L RFT-I group; preoperative creatinine <1.25 mmol/L but postoperative creatinine >1.25 mmol/L RFT-II group; preoperative creatinine >1.25 mmol/L but postoperative creatinine <1.25 mmol/L RFT-III group; and preoperative and postoperative creatinine >1.25 mmol/L RFT-IV group. Results: Of the 284 cases, 62% required intensive care after surgery. While 95.4% of the patients were discharged, 4.6% did not survive. No renal dysfunction was observed in the RFT-I group (68.7%, n=195) (preoperative and postoperative creatinine <1.25 mmol/L). In the RFT-II group (17.6%, n=50), renal dysfunction (creatinine >1.25 mmol/L) developed due to postoperative surgical stress (creatinine <1.25 mmol/L). In patients in the RFT-III group (6%, n=17), preoperative renal dysfunction (creatinine >1.25 mmol/L) improved with postoperative care (creatinine <1.25 mmol/L). In the RFT-IV group (7.7%, n=22), preoperative renal dysfunction (creatinine >1.25 mmol/L) did not improve postoperative renal dysfunction despite appropriate perioperative fluid replacement. Conclusion: Our study observed an increase in postoperative urea and creatinine values due to surgical stress in our patient group aged 90 and over, who had limited physiological reserves. However, it has been shown that improvement in renal function tests can be achieved with appropriate fluid replacement and postoperative intensive care treatment in patients with postoperative or preoperative renal dysfunction. Our rates of postoperative renal dysfunction due to surgical stress were lower and did not change mortality.